Tumor-associated macrophages: new insights on their metabolic regulation and their influence in cancer immunotherapy - Xiao, Li; Wang, Qiao; Peng, Hongling (Frontiers in Immunology, 2023)
Tumor-associated macrophages (TAMs) are a dynamic and heterogeneous cell population of the tumor microenvironment (TME) that plays an essential role in tumor formation and progression. Cancer cells have a high metabolic demand for their rapid proliferation, survival, and progression. A comprehensive interpretation of pro-tumoral and antitumoral metabolic changes in TAMs is crucial for comprehending immune evasion mechanisms in cancer. The metabolic reprogramming of TAMs is a novel method for enhancing their antitumor effects. In this review, we provide an overview of the recent research on metabolic alterations of TAMs caused by TME, focusing primarily on glucose, amino acid, and fatty acid metabolism. In addition, this review discusses antitumor immunotherapies that influence the activity of TAMs by limiting their recruitment, triggering their depletion, and re-educate them, as well as metabolic profiles leading to an antitumoral phenotype. We highlighted the metabolic modulational roles of TAMs and their potential to enhance immunotherapy for cancer.